Restrukturisasi Pembiayaan Selama Pandemic Covid-19 Di Bank Muamalat Madiun - Haidar Ali; Adi Setiawan (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
The occurrence of Pandemic Covid-19 resulted in Islamic banking must do a way to relieve the burden of Affected Customers. Efforts made by Islamic banks in order to assist customers in order to resolve their obligations, one of which is restructuring financing. This study has the aim of analyzing restructuring barriers and strategies in the completion of financing during the Covid Virus Pandemic - 19 at Bank Muamalat Madiun Branch Office. The research method uses using a qualitative method approach to analyze descriptively. The results of this study are three, namely (1) problematic financing factor in Bank Muamalat occurs because of external factors, namely the plague of Pandemic Covid-19 that hit Indonesia and the world. (2) The obstacles in the completion of Bank Muamalat's bank financing of the Madiun branch office occur due to the verification problem of administrative files that must be fulfilled by the Customer. (3) Strategies in Completion of Bank Muamalat Bank Financing Madiun Branch Office Using financing Restructuring Through: Rescheduling, Reconditioning, and Restructuring In accordance with the provisions of Bank Indonesia.